The Design of Microcontroller-Based Detection Tools and Rat Pest Repellent on Rice Seeds - Mu'azaidin Nur Kusna; Zainal Abidin; Ulul Ilmi (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2021)
The control of rat pest in rice nurseries to obtain increased production continues to be done. In an effort to overcome the problem of rat pest various alternative controls have been carried out, both in technical culture, physical mechanics, and chemically. To reduce the undesirable effects of using chemicals to control rat pets, it is necessary to use other alternative rat pets control. Based on these problems, this study conducted various test to create a design that could be used to repel rat pests. The method used includes electrical and systematic design. The steps taken include the sate of literature study then designing, manufacturing hardware and software integrating the system and testing and analyzing the system. Considering these theories, it can find out the programming of microcontrollers, LDR sensors, Cameras, Internet Networks, NE555, Solar Panels, and Accu.This study uses several tests, including testing the LDR sensor, Camera, Internet Network, NE555, Solar Panel and Accu. LDR sensor is functions to detect rat objects, cameras to take video directly, internet network to send video from the microcontroller to the user, NE555 to emit ultrasonic soungd waves to repel rat pests, solar panels as a source of electrical energy, and accu as electrical energy storage that produced solar panels. From all of test above we get results when the LDR Sensor detects a rat then the NE555 will emit ultrasonic waves, then the camera sends video via iot to usser.